2013
DOI: 10.1097/aln.0b013e31828afc16
|View full text |Cite
|
Sign up to set email alerts
|

Propofol and Thiopental Suppress Amyloid Fibril Formation and GM1 Ganglioside Expression through the γ-Aminobutyric Acid A Receptor

Abstract: Background: The incidence of Alzheimer disease may increase after surgical interventions. Amyloid β-protein (Aβ) fibrillogenesis, which is closely related to Alzheimer disease, is reportedly accelerated by exposure to anesthetics. However, the effects of GM1 ganglioside (GM1) on Αβ fibrillogenesis have not yet been reported. The current study was designed to examine whether the anesthetics propofol and thiopental are associated with Αβ assembly and GM1 expression on the neuronal cell surface.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…We have previously reported that insulin regulates the expression and distribution of GM1 in neuronal DRM through PI3K [28]. Moreover, our recent study found that propofol and thiopental inhibited the formation of Аb assemblies by decreasing GM1 expression in neuronal DRM through the GABAAR [22]. In the present study, we found that GM1 expression in neuronal DRM and synaptosomes was reduced by midazolam and that these effects were mediated through the GABAAR.…”
Section: Discussionsupporting
confidence: 40%
See 2 more Smart Citations
“…We have previously reported that insulin regulates the expression and distribution of GM1 in neuronal DRM through PI3K [28]. Moreover, our recent study found that propofol and thiopental inhibited the formation of Аb assemblies by decreasing GM1 expression in neuronal DRM through the GABAAR [22]. In the present study, we found that GM1 expression in neuronal DRM and synaptosomes was reduced by midazolam and that these effects were mediated through the GABAAR.…”
Section: Discussionsupporting
confidence: 40%
“…The present Аb assembly experiments were performed in a cell-free system using seed-free Аb solutions and GM1 liposomes. Recently, we found that propofol and thiopental inhibited the formation of GM1 liposome-induced Аb assemblies from soluble Аb [22]. Although further investigation is required, the findings of the present study indicate that midazolam directly inhibits the formation of GM1 liposome-induced Аb assemblies through molecular interactions (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…) and that PDMP, insulin, propofol, and thiopental inhibited the GM1 expression levels in PC12N cells (Yamamoto et al . , , ). To investigate whether GM1 synthesis is inhibited by leptin, we pre‐treated neurons with chloroquine before leptin treatment, following which the cells were treated with leptin in the presence of chloroquine.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we recently found that insulin, propofol, and thiopental inhibited the formation of Aβ fibrils on the neuronal cell surface through the reduction in GM1 expression in the detergent‐resistant membrane microdomains (DRMs) of neuronal membranes (Yamamoto et al . , ), whereas insulin resistance had the reverse effect (Yamamoto et al . ).…”
mentioning
confidence: 99%